COVID-19, A Complex Emotional Well-Being Challenge: A Path to Recovery in Nepal - Jeeawody, A. Basseer; Adhikari, Raju; Sivamalai, Sundram (Nepal Journal of Science and Technology, 2021)
Mental health and emotional well-being remain an urgent civil societies’ global burden. There is an increasing prevalence of mental health and emotional well-being problems in our societies and nations. There are severe implications from these connected with the Coronavirus 2019 (COVID-19). The COVID-19 has produced the gravest disruption to our nations’ health, education, employability, economy, social structure, and mobility.The pandemic has placed humanity in a global emergency with long-term implications. The population’s emotional well-being, including stress related disorders has been severe and likely to be prolonged. The burden of COVID-19 is escalating despite governmental and non-governmental resources, voluntary, religious organisations, and philanthropic efforts. Nations must address the psycho-social conditions of their population as a public health imperative by identifying the peoples’ emotional well-being needs and prioritise strategies to enable their capacity for ‘doing good’ and ‘feeling of goodness’. The Emotional Well-being Institute (EWBI) advocates the significance of ‘feeling goodness’, and that innovative approaches and research initiatives are urgently needed to understand emotional well-being attributes and their impact on overall mental health. Emotional well-being is a broad concept, one that includes several aspects of our everyday lives. There needs to be a multi-dimensional and a whole-of-society approach when addressing the emotional well-being of highly vulnerable societies and nations, such as Nepal.